M11 A randomised controlled feasibility trial of a physical activity behaviour change intervention compared to social interaction in huntington's disease. (13th September 2016) - Busse, Monica; Quinn, Lori; Drew, Cheney; Kelson, Mark; Trubey, Rob; McEwan, Kirsten; Jones, Carys; Townson, Julia; Dawes, Helen; Edwards, Rhiannon Tudor; Rosser, Anne; Hood, Kerenza
Abstract : Background: Regular physical activity has health benefits for people with Huntington's disease (HD), however consistent engagement is challenging. We report the results of a single blind, multi-site, randomised controlled feasibility trial of a physical activity intervention in HD. Methods: Participants were randomly assigned to physical activity or social contact control interventions. The primary outcome was feasibility. Short-term benefit was assessed with the Physical Performance Test (PPT), a measure of functional ability. A range of exploratory outcomes including home and community mobility (Life Space), self-efficacy (Lorig), physical activity (International Physical Activity Questionnaire (IPAQ)), as well as disease-specific measures of motor and cognitive function were evaluated. Intervention fidelity and delivery costs were established. The trial was registered (ISRCTN 65378754 (13/03/2014)). Results: We recruited 46 people with HD; 22 were randomised to the physical intervention (n = 16 analysed); 24 to social contact (n = 22 analysed). Retention, fidelity and adherence met pre-determined criteria. IPAQ scores in the physical intervention group were 142% higher (1.42; 95% CI: [−22%%, 653%]); and self-efficacy for exercise (1.6; 95% CI: [0.6, 2.7]) was also higher. Life Space scores were 12 points different between groups; 95% CI: [−2, 27]. Cognitive function was better in the physical intervention group with 2·9 more correct responses (95% CI: [0.01, 5.9]) on the Symbol Digit Modality test. There were no differences in other exploratory outcome measures and in particular no between-group differences in the PPT (treatment effect: 0.3, 95% CI: [−2.1, 2.7]). Mean (SD) physical intervention per session cost was £56.97 (£34.72). Conclusion: A physical activity coaching intervention is feasible, can improve self-efficacy, physical activity behaviours and cognitive function in people with HD and represents excellent value for money in a devastating disease. Funding: Health and Care Research Wales.